Sistem Manajemen Operasional Jasa Travel Kendaraan Dalam Meningkatkan Pelayanan Perusahaan - Cahya Vikasari (Politeknik Harapan Bersama, 2018)
Car rental is a growing business that runs rapidly. Competition of travel business is getting strict and business development is getting rapidly. They can boost companies to improve quality and service to their consumers. The problem which always happens in processing travel business, i.e., manual data processing using book. It can give risk for losing data and duplication process, and also the data that does not automatically recapped until the report of income and other information are not up to date. It is needed that there is a system for supporting process of travel operational management. The method that used in the research was a method of software development, i.e., waterfall. The findings of the research is the system that can facilitate the process of travel operational management until it can make the available process more effective, improve the service to consumers, facilitate to search for data that relevant to vehicle travel data.